PENINGKATAN KINERJA GURU OLEH KEPALA SEKOLAH UNTUK MENINGKATKAN MUTU PEMBELAJARAN SMP PLUS DHARMA AGUNG PASEH - Ujang Cepi Barlian; Hasbullah Lau; Raindra Anggraeni Rosmalinda; Cucu Amirah (Bajang Institute, 2022)
The general objective of this study is to obtain an overview of improving teacher performance by principals to improve the quality of learning in junior high schools. This study used descriptive qualitative method. The results of the study are, 1) Planning shows that planning aspects have been adapted to the conditions and abilities of the school concerned, 2) Organizing shows that it is in accordance with organizing principles, 3) Implementation has entered the program criteria in implementing teacher performance, 4) Evaluation is appropriate. with those determined by conducting an assessment (supervision procedures), 5) The obstacle is the lack of ability to carry out effective supervision and lack of motivation from the teacher, 6) The solution is the principal's motivation and encouragement to teachers to be enthusiastic in improving their performance. The conclusion of this research is the improvement of teacher performance by the principal to improve the quality of learning at SMP Plus Dharma Agung Paseh has been carried out well and can improve the quality of learning.